Biochemical studies of taste sensation: monoclonal antibody against L-alanine binding activity of catfish taste epithelium. - Goldstein, N I (1982)
The L-alanine taste receptors of the channel catfish Ictalurus punctatus provide a useful biochemical model for studying taste receptor mechanisms. Mouse hybridomas that synthesize monoclonal antibodies have been produced. The antigen used to activate mouse spleen cells was the plasma membrane fraction obtained from the taste receptor-containing epithelium of the channel catfish. The spleen cells were fused with myeloma cells, Sp2/0-Ag14, to form hybridomas. To demonstrate inhibition of ligand binding by the product of these hybridomas, a catfish membrane fraction (fraction P2) was incubated with the antibody-containing preparation prior to assaying for L-[3H]alanine binding activity. We thereby demonstrated inhibition of binding of the taste ligand L-alanine to fraction P2. This approach should prove useful in further studies of receptor binding and transduction events in taste receptors.